(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the linguacultural features of comparisons are studied in a comparative aspect. In particular, the national specificity of comparisons in the Uzbek language directly reflects the social, cultural and everyday life of the Uzbek people, the expression of the character and characteristics of the Uzbek people and shows that it is reflected in literary and artistic creativity. The language is aimed at revealing the possibilities of linguistic and cultural unity using the example of the “Great kingdom” of Muhammad Ali.